2019
DOI: 10.5812/ijp.97306
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Celiac Disease in Children with Type 1 Diabetes Mellitus in the South of Turkey

Abstract: Background: Type 1 Diabetes Mellitus (DM), autoimmune disorders, relatives of celiac patients have higher risk of developing celiac disease (CD) because they share the same HLA type. Celiac disease and type 1 DM are autoimmune and common in children. According to international guidelines, serological screening for CD in children and adults with type 1 DM is recommended but there is no consensus on how often it will be performed. Objectives: We aimed to investigate the prevalence of CD in children with type 1 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 29 publications
(32 reference statements)
3
17
0
Order By: Relevance
“…In a systematic review, the prevalence of celiac disease in patients with type 1 DM was reported to be approximately six times higher than in the general population[ 91 ]. The prevalence of celiac disease was reported to be 2.4%-16.4% in children with type 1 DM[ 92 - 95 ]. There is consensus about initial screening for celiac disease in newly diagnosed DM patients, but it is not clear when and how often to screen for celiac disease and initiate a gluten-free diet in asymptomatic patients[ 93 ].…”
Section: Associated Diseases With Celiac Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…In a systematic review, the prevalence of celiac disease in patients with type 1 DM was reported to be approximately six times higher than in the general population[ 91 ]. The prevalence of celiac disease was reported to be 2.4%-16.4% in children with type 1 DM[ 92 - 95 ]. There is consensus about initial screening for celiac disease in newly diagnosed DM patients, but it is not clear when and how often to screen for celiac disease and initiate a gluten-free diet in asymptomatic patients[ 93 ].…”
Section: Associated Diseases With Celiac Diseasementioning
confidence: 99%
“…It has been recommended that screening test for CD should be done at the time of type 1 DM diagnosis and then every 2 years[ 96 ]. In another study, it was recommended that children diagnosed with type 1 DM should be screened for celiac disease once a year for the first 5 years[ 92 ]. In other studies, it has been recommended that serological screening tests for celiac disease should be done within the first 2 years when the diagnosis is made, then 5 years after the diagnosis and if there is any symptom suggestive of CD[ 93 , 97 ].…”
Section: Associated Diseases With Celiac Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…11 Internationally, the prevalence ranges from 3%-12%. [12][13][14] There are multiple possible reasons for the low prevalence of confirmed CD in this study, including early screening of asymptomatic T1DM patients, the low referral rate for endoscopy by the treating physician, patient or family refusal to undergo an endoscopy, and loss of patient follow-up at the gastroenterology service.…”
Section: Discussionmentioning
confidence: 97%
“…The risk of developing CD is higher in type 1 Diabetes Mellitus (DM), Down syndrome, Turner syndrome, autoimmune disorders, and relatives of celiac patients sharing the same type of HLA [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%